2001
DOI: 10.1034/j.1600-0749.2001.140411.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Hormonal Regulation of Pigmentation in Human Ocular Melanocytes

Abstract: The purpose of this study was to examine some of the factors that may be relevant to regulating pigmentation in the human eye, specifically whether choroidal and iridial melanocytes are sensitive to regulation by epithelial and stromal cells and alpha-melanocyte stimulating hormone (alpha-MSH). Human choroidal and iridial melanocytes were established in culture and co-cultured with epithelial cells and stromal cells derived both from skin and from eye in order to determine their influence on choroidal and irid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…It has been demonstrated that fibroblasts influence dopa oxidase activity in melanocytes. [19][20][21] An additional source of signals for melanocyte proliferation and differentiation derives from extracellular matrix proteins. 22 Pigmented lesions that appear on excision scars of melanocytic tumours pose two main problems.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that fibroblasts influence dopa oxidase activity in melanocytes. [19][20][21] An additional source of signals for melanocyte proliferation and differentiation derives from extracellular matrix proteins. 22 Pigmented lesions that appear on excision scars of melanocytic tumours pose two main problems.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the occurrence of ocular albinism, characterized by depigmentation of the eye but not the skin, suggests different melanogenesis pathways in ocular and cutaneous melanocytes [26]. To the contrary, however, recent evidence indicates that ocular melanocytes express melanocortin 1 receptors (MC1R) on their surface and are responsive to AE-melanocytestimulating hormone, the agonist for these receptors [28].…”
Section: Discussionmentioning
confidence: 99%
“…They synthesise melanin, which has important protective functions such as absorption of UV light and binding of radicals and toxic substances [1,2]. In contrast to cutaneous melanocytes, choroidal melanocytes do not synthesise melanin in vivo, but they can do so in vitro [3][4][5][6]. Cultures of normal cutaneous or choroidal melanocytes are useful in vitro models for the study of melanocyte biology or melanocyte transformation into melanoma cells, and they can also be used for tissue engineering and the designing of tissues for transplantation purposes.…”
Section: Introductionmentioning
confidence: 99%